1997
DOI: 10.1159/000244508
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Lipoprotein Composition and Corresponding Apolipoproteins in the Newly Hatched Male and Female Broiler Chick from Two Different Age Flocks

Abstract: The purpose of this experiment was to investigate the effects of breeder flock age (30 vs. 39 weeks) and sex of the newly hatched chicks on lipoprotein composition and apolipoprotein AI (apoAI) and B (apoB) concentrations. Additionally, fast protein liquid chromatography (FPLC) was used to evaluate which lipoprotein fraction (VLDL vs. LDL vs. HDL) carried the bulk of cholesterol in newly hatched chicks. Other lipoproteins were separated by density gradient ultracentrifugation to determine their chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Additionally, the transfer of this gross energy to the developing duck embryo during incubation is more efficient. Increased breeder age was associated with increased percentage RYW and RLW, which was consistent with the findings of Latour et al [10] and Applegate et al [8].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the transfer of this gross energy to the developing duck embryo during incubation is more efficient. Increased breeder age was associated with increased percentage RYW and RLW, which was consistent with the findings of Latour et al [10] and Applegate et al [8].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, different lipoproteins predominate at different times during incubation and the early posthatch period. At hatch, cholesterol is carried equally between LDL and HDL particles [3], but by 3 days of age, HDL becomes the predominate carrier of circulating cholesterol [16]. Lazier et al [17] observed that the level of mRNA for ApoB, the primary protein of VLDL and LDL, increases in the vascular yolk sac membrane through incubation.…”
Section: Discussionmentioning
confidence: 99%
“…1.67. The sum of these components (PRO, TG, free cholesterol, CE, and PL) represents nearly 100% of the lipoprotein composition [3]. Hence, relative changes in these components within VLDL and LDL may provide some clues of their altered nature.…”
Section: Lipid Analysis Of Lipoproteinsmentioning
confidence: 99%
See 1 more Smart Citation